1975
DOI: 10.1159/000301513
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Studying Oviductal Physiology

Abstract: In studying oviductal physiology, it is important to sort out the complex interrelationships between muscle, cilia, nerves and secretory processes as they each of themselves, or in concert, effect gamete transport. In this review, a variety of physiological techniques and bioengineering approaches which have been used to monitor contractile and ciliary activity, are described and critically evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The microscope stage was tem perature-controlled at 37 °C. A photoelectric sensor mounted in the microscope eye piece was used to measure the rate of cilia beating [3]. The output of the photo electric sensor was recorded with an oscillograph and the records analyzed by hand to determine the cilia beat frequency.…”
Section: Ciliary Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The microscope stage was tem perature-controlled at 37 °C. A photoelectric sensor mounted in the microscope eye piece was used to measure the rate of cilia beating [3]. The output of the photo electric sensor was recorded with an oscillograph and the records analyzed by hand to determine the cilia beat frequency.…”
Section: Ciliary Activitymentioning
confidence: 99%
“…Ciliary transport was studied in vitro by using procedures developed previously in our laboratories [3]. An oviduct from an ovulatory rabbit was slit open longi tudinally along the antimesosalpingeal border with iridectomy scissors.…”
Section: Ciliary Transport In Vitromentioning
confidence: 99%
“…Regulation of ciliary motility is therefore important to facilitate the meeting of gametes and the subsequent transport of the fertilized ovum to its implantation site. Several factors have been reported to affect tubal ciliary motility including progesterone (P 4 ) [3-6], estradiol [3], interleukin 6 [7], prostaglandins [8,9], angiotensin II [10] and Ca 2+ [11]. …”
Section: Introductionmentioning
confidence: 99%
“…The reasons for this failure of definition are both technological and biological. Several investigators have measured oviductal contractile activity in many species by utilizing intra-and extra-luminal sensors in vivo and in vitro (Blandau, Boling, Halbert & Verdugo, 1975). To date studies utilizing mechanical measurements of contractile activity have not shown any relation¬ ship of such parameters as intraluminal pressure or wall tension to ovum transport rates.…”
Section: Physiological Functionsmentioning
confidence: 99%